Physiological and Biochemical Responses of Cucumis melo L. Chloroplasts to Low-Phosphate Stress - Li, Pengli; Weng, Jinyang; Zhang, Qing; Yu, Liyao; Yao, Qi; Chang, Liying; Niu, Qingliang (Frontiers in Plant Science, 2018)
Phosphorus (P) is a limiting plant soil nutrient. Long-term low inorganic phosphate (Pi) irreversibly damages plant cells and hinders plant growth. Plants have evolved several adaptive biochemical, physiological, and developmental responses to low-Pi stress. However, little is known about chloroplast responses to low-Pi stress. In this study, we used physiological and biochemical analyses to investigate melon chloroplast responses to low-Pi stress. The results indicated that low-Pi stress impeded melon seedling growth and reduced its dry matter content by inhibiting the photosynthesis. Low-Pi stress reduced the P content in shoots, which inhibited ATP synthase (ATP-ase) activity, and disturbed the proton and electron transport efficiency on chloroplast photosynthetic electron transport chain. In addition, low-Pi stress induced reactive oxygen species (ROS) production in the leaves, which caused membrane peroxidation. Therefore, redox homeostasis was not maintained, and the melon leaves presented with symptoms of photooxidative stress. To mitigate photoinhibition, the melon plants initiated non-photochemical chlorophyll fluorescence quenching (NPQ) initiated by acidification of the thylakoid lumen to dissipate excess excitation energy, significantly improved ROS-scavenging enzyme activity. Based on these experimental results, we concluded that low Pi inhibited photosystem activity and caused photooxidative stress and photoinhibition. To alleviate these negative effects, the plant activated its NPQ mechanism, alternative electron transport pathways, and antioxidant system to protect its chloroplasts.